Australian literary award winners : updated list of winners of the most prestigious awards given for literary achievement in Australia. - Box Hill-Doncaster Regional Library ([Box Hill, Vic.] : Box Hill-Doncaster Regional Library, 1987)
Includes the library's locations.
Cover title.
Keywords: Literary prizes -- Australia